PTH-176 Predicting histological remission in patients with coeliac disease on a gluten free diet. (22nd June 2015) - Mooney, PD; Wong, S; Kurien, M; Burden, M; Sanders, DS
Abstract : Introduction: Up to 30% of patients with celiac disease (CD) will have persistent symptoms despite the introduction of a gluten free diet (GFD). Assessment of adherence in celiac disease can involve any combination of patient self-reporting adherence, dietetic assessment, serology and biopsy with histology. Histology is considered to be the 'gold standard' but this requires a repeat endoscopic examination with its associated risks and problems with tolerance. As a result surrogate markers of persistent gluten exposure and histological changes such as serology are frequently used but the relationship between serology and persistent histological changes is not linear. A structured interview with a dietician has been shown to be the most accurate method of assessing GFD adherence however this is time consuming and requires extra clinic visits. The aim of this study was to assess the usefulness of two novel options. Firstly a previously internally validated scoring system for assessing GFD adherence (which has never been externally validated) and secondly a rapid deamidated gliadin peptide based point of care test (POCT, Simtomax) for the prediction of persistent villous atrophy (VA). Method: All patients with known CD and persistent symptoms coming to a specialist CD endoscopy list for the re-assessment of histology were invited to take part. All patients were tested for Endomysial Antibody (EMA), tissue transglutaminase (tTG), immunoglobulins and the POCT. They were also asked to complete a questionnaire to calculate a 5 point score (0–4) with a high score representative of improved adherence to a gluten free diet. All patients underwent gastroscopy with at least 4 biopsies from the second part of the duodenum and 1 to 2 biopsies from the bulb. Results: 94 patients (77% female, mean age 52.6) were recruited between April 2013 and December 2014. Median duration of GFD was 84 months (range 6–768). 36 (38.3%) patients had persistent VA on duodenal biopsy. The POCT was the most sensitive marker with 63.4% of patients with VA having a positive test. EMA was the most specific surrogate marker at 82.8% although it was highly insensitive with only 33.0% of patients with VA having a positive EMA. The adherence score could not be reliably used to predict VA with a sensitivity of only 30.6%. Conclusion: An accurate surrogate marker for VA could reduce the number of endoscopies required. In this cohort the POCT had the best sensitivity, detecting 23/36 (63.4%) cases of villous atrophy, however this is pilot data and further work is required. It may be that additive methods for assessing adherence could achieve 100% sensitivity. Disclosure of interest: P. Mooney: None Declared, S. Wong: None Declared, M. Kurien: None Declared, M. Burden: None Declared, D. Sanders Grant/ Research Support from: Received research grants from BHR Pharmaceuticals and Tillotts Pharma for investigator led studies into coeliac disease.